Evaluation of propofol as an anesthetic in swine tracheal transplant surgery - Gaviria, Elmer J.; Restrepo, Juan G.; Marín, Juan D.; Arango, Gonzalo; Aramburo, Diego; Franco, Felipe; Tintinago, Luis F. (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary Because the swine have been used as an ideal animal model for different medical investigations, it has been useful to the advance in vital organs transplant field. The trachea transplant is a surgical procedure which requires special conditions in anesthetic depth and muscular relax, for a long period, and in addition, an excellent intra and post-operatory analgesic. The aim of this study was to use a combination of xylacine and ketamine, as premedication and evaluate propofol as a general anesthetic in trachea transplant donor or recipient pigs. All the methodology was under the approval of the Committee of Ethics for the Experimentation with Animals of the University of Antioquia. Ten donors and 10 recipients female Yorkshire pigs having a body weight of about 30 kg were used. Trachea extraction from a donor and its transplantation to a recipient in the same surgical procedure was performed. The average body weight (PP) was 30 ± 2.92 kg for both the groups, the average value were as follows: time of recumbency (TR) 8.25 ± 2:85 min; latency period (PL) 6.05 ± 1.73 min, (for both groups); surgical time (TQ) for donors and recipients was 80 ± 0.02, and 247 ± 0.02 min, respectively; heartbeat rate (FC) 90.34 ± 8.14 bpm, O2 saturation (SO2) 95.47 ± 1.79%; exhaled PCO2 31.13 ± 1.89 mmHg; temperature (T) for both groups was 37.51 ± 0.74 oC. The mean arterial pressure average (PAM) for both group was 65.47 ± 5.94 mmHg; the average time of esternal recumbecency (TRE) for donor female pigs was 16.50 ± 4.09 min, and the average time to stand up (TP) for swine recipients was 30.70 + 3.27 min. These results indicate that Propofol can be considered as a safe anesthetic for use in continuous perfusion. Since it has not an analgesic effect it is strongly recommended to combine it with opioids during anesthetic-surgical procedures; it can be also used with neuromuscular preanesthetics or inhaled anesthetics. Resumen Los cerdos se han utilizado como modelo animal ideal para diversas investigaciones médicas; han sido útiles para el avance en el trasplante de órganos. El trasplante de tráquea es un procedimiento quirúrgico que requiere condiciones especiales en profundidad anestésica y relajación muscular por un período largo, y además, una analgesia intra y del postoperatoria excelente. Nuestra investigación utiliza una combinación de xylacine y ketamina, como premedicación y evaluar el propofol como anestésico general en cerdos donantes y receptores en quienes el trasplante de la tráquea sería hecho. Toda la metodología contó con la aprobación del Comité de Ética para la Experimentación con los Animales de la Universidad de Antioquia. Utilizamos 10 donantes y 10 cerdos raza Yorkshire hembras con un peso corporal de cerca de 30 kilogramos. Se realizó la extracción de la tráquea de un donante y el trasplante a un receptor en el mismo procedimiento quirúrgico. El peso corporal (PP) fue de 30 ± 2.92 kg para todo el grupo, el tiempo de recumbencia (TR) para ambos grupos fue de 8.25 ± 2.85 min, el período de latencia (PL) para ambos grupos fue de 6.05 ± 1.73 min, el promedio de tiempo quirúrgico (TQ) para los donantes fue de 80 min ± 0.02, el TQ de los receptores fue de 247m ± 0.02. La presión arterial media (PAM) para todo el grupo fue de 65.47 ± 5.94 mmHg, el promedio de frecuencia cardiaca (FC) para ambos grupos fue de 90.34 ± 8.14 ppm, el promedio de saturación de oxigeno (SO2) fue de 95.47 ± el 1.79% y el CO2 respirado fue de 31.13 ± 1.89 mmHg y el promedio de la temperatura (t) para ambos grupos fue de 37.51 ± 0.74 oC. La tiempo de recumbencia esternal (TRE) para las cerdas donantes fue de 16.50 ± 4.09 min y el tiempo para pararse (TP) para los receptores fue de 30.70 ± 3.27 min. El propofol se puede considerar como anestésico seguro para el uso en la perfusión continua durante la anestesia. Puesto que no tiene un efecto analgésico se recomienda combinarlo con opioides durante procedimientos anestésico-quirúrgicos; puede también ser utilizado con preanestésicos, relajantes musculares o anestésicos inhalados.